Multi-photon absorption and third-order nonlinearity in silicon at mid-infrared wavelengths - Wang, Ting (2014)
Silicon based nonlinear photonics has been extensively researched at telecom wavelengths in recent years. However, studies of Kerr nonlinearity in silicon at mid-infrared wavelengths still remain limited. Here, we report the wavelength dependency of third-order nonlinearity in the spectral range from 1.6 µm to 6 µm, as well as multi-photon absorption coefficients in the same range. The third-order nonlinear coefficient n2 was measured with a peak value of 1.65 × 10−13 cm2/W at a wavelength of 2.1 µm followed by the decay of nonlinear refractive index n2 up to 2.6 µm. Our latest measurements extend the wavelength towards 6 µm, which show a sharp decrement of n2 beyond 2.1 µm and steadily retains above 3 µm. In addition, the analysis of three-photon absorption and four-photon absorption processes are simultaneously performed over the wavelength range from 2.3 µm to 4.4 µm. Furthermore, the effect of multi-photon absorption on nonlinear figure of merit in silicon is discussed in detail.